PIDS 2010 economic policy monitor: Fiscal space, investment, and poverty alleviation - Majuca, Ruperto P. (Animo Repository, 2011)
The first issue of the PIDS Economic: Policy Monitor focuses on three related issues: fiscal space, investment, and poverty alleviation. One of the main goals of development is inclusive economic growth which ensures that economic growth and development are accompanied by a reduction in poverty incidence. Chapter 1 shows that the Philippine economy grew by 7.3 percent in terms of the gross domestic product (GDP) in 2010, a feat that was beyond the expectations of all analysis. The challenge is to sustain this momentum and make economic growth more inclusive so that poverty may be reduced. The most direct way to ensure the "inclusiveness" of the growth is to increase the employment rate in the country. This in turn can be addressed by raising the country's investment rate which is one of the lowest in East Asia. Among the major factors for the low investment rate in the Philippines are the country's poor quality of physical infrastructure, weak institutions, and unstable macroeconomic environment. To address these supply side constraints in achieving a higher investment rate in the Philippines, it is imperative that the government consolidates its fiscal position to close the national deficit (3.9% of GDP in 2010) in order to have the needed financial resources. Improved tax administration is the most effective and efficient way to address the deficit. Another means is the rationalization of other expenditure items and sources of government deficit. In both cases, however, a great deal of institutional strengthening and political will are required. ln the medium term, the key policy issues relate ro diversifying the sources of economic growth that will allow greater employment in the more productive sectors of the economy. And one significant point to be considered here is whether the services sector can be the driver of the Philippine economy or nor. This has major implications insofar as the policy measures that can lead the country's economy to a path of sustainable growth are concerned. Chapter 2 deals with how the national government can consolidate its fiscal position in order to be able to finance the Millennium Development Goals (MDGs) and achieve inclusive growth for the economy. With the more expansionary stance taken by the government in 2009 as part of its effort to shield the economy from the effects of the global financial and economic crisis, of 2008/2009, the government's fiscal deficit jumped to 3.9 percent of GDP and the national government debt began co rise vis-a vis the GDP. The fiscal deficit is also being projected to remain high at 3.8 percent of GDP in 2010 and 3.4 percent of GDP in 2011. ln view of this, turning around the national government's fiscal health should definitely be high on the policy agenda. In previous episodes of fiscal consolidation, the easiest way to address the fiscal imbalance was by cutting expenditures. Unfortunately, this option of underspending on basic social services and infrastructure and the concomitant service deficit in these sectors in earlier years had put the Philippines' attainment of the MDGs ar risk. The fiscal sustainability analysis undertaken in this chapter indicates that national government revenues need to increase from 14.3 percent of GDP in 2009-2010 to 17.6-18.0 percent in 2012-2016 if fiscal consolidation were to be achieved while providing adequate budgetary support for the much-needed basic social services and infrastructure to achieve inclusive growth and the MDGs.